Efficacy and Safety of Different Immunosuppressive Therapies in Patients With Membranous Nephropathy and High PLA2R Antibody Titer - Deng, Le; Huang, Qipeng; Wang, Jiang; Luo, Kaiping; Liu, Jiarong; Yan, Wenjun; Jiang, Fang; Xu, Gaosi (Frontiers in Pharmacology, 2022)
Background To evaluate clinical features and prognosis and therapy option of patients with different risk ranks based on PLA2Rab (antibody against the M-type phospholipase-A2-receptor) level in seropositive M-type phospholipase-A2-receptor (PLA2R)-associated membranous nephropathy (MN) in a large sample size, multi-center study. Method Based on the unvalidated cut-off value of PLA2Rab above 150 RU/mL as one of clinical criteria for high risk of progressive kidney function loss in MN according to 2020 Kidney Disease: Improving Global Outcomes (KDIGO) draft guidelines recommendation, a total of 447 patients received cyclophosphamide (CTX) or tacrolimus (TAC) combined with corticosteroids treatment for 12 months were divided into high titer (> 150RU/mL) group and non-high titer (20-150RU/mL) group, which were subdivided into CTX subgroup and TAC subgroup. The overall cohort was classified into CTX group and TAC group as well. Clinical parameters levels and remission rates were recorded at 3, 6, and 12-month follow-up. PLA2Rab was tested by enzyme-linked immunosorbent assay. Results Patients with high titer PLA2Rab were associated with more severe proteinuria and hypoalbuminemia compared to those with non-high titer antibody, accompanied by lower complete remission (CR) and total remission (TR) rates at 3, 6, 12 months, which even took longer to remission. Similar remission rates were observed in CTX group and TAC group. PLA2Rab level at baseline was an independent predictive factor for CR and TR. In the high titer group, CR and TR rates in CTX subgroup were significantly higher than those in TAC subgroup at 12 months. Conclusions High-risk rank patients with PLA2Rab level above 150RU/mL have higher disease activity and worse prognosis among patients with seropositive PLA2R-associated MN, even under different immunosuppressive therapeutic models, and baseline PLA2Rab level was an independent predictive factor for CR and TR, moreover, CTX treatment achieves more CR and TR than TAC therapy in patients with PLA2Rab level above 150RU/mL, which may predict the activity of the disease and prognosis while providing guidance of the therapeutic option for seropositive PLA2R-associated MN.